Faktor Yang Mempengaruhi Keputusan Pembelian Skincare Remaja Di SMAN 1 Bantaeng - Aqilah Zalsabilla Marzuki; Fatmah Afrianty Gobel; Mansur Sididi (Window of Public Health Journal, 2026)
Adolescent girls' interest in physical appearance is driving increased skincare purchases. Competition from local brands is increasingly fierce, driven by social media advertising and efforts to strengthen brand image. For Muslim teenagers, halal labels and BPOM permits are important considerations. However, the presence of dangerous products that continue to circulate despite having BPOM permits shows that distribution permits alone do not guarantee product safety. Adolescents' limited awareness of active ingredients underscores the importance of research into the factors influencing skincare purchasing decisions. This study aims to determine the relationships among halal labels, BPOM labels, ingredient safety, and skincare side effects on purchasing decisions among adolescent girls at SMAN 1 Bantaeng. This study used a quantitative, cross-sectional design. The sample consisted of 40 female students in grades X, XI, and XII. The research instrument was a questionnaire, and data analysis used the chi-square test. The results showed no relationship between halal labels (p = 0.736), BPOM labels, ingredient safety (p = 0.850), and purchasing decisions. However, there was a significant relationship between side effects of use (p = 0.005) and purchasing decisions. The results showed that side effects influence purchasing decisions. It is recommended to research other factors that affect skin health.